207k views
1 vote
Solve for n.
11(n − 1) + 35 = 3n
0 n =-6
n=-3
0 n=3
0 7 = 6

User Versatile
by
5.0k points

2 Answers

5 votes

Answer:

n = -3

Explanation:

11(n - 1) + 35 = 3n

Expand the brackets.

11n - 11 + 35 = 3n

Add the terms -11 and 35.

11n + 24 = 3n

Subtract 24 and 3n on both sides.

11n - 3n = -24

8n = -24

Divide 8 into both sides.

8n/8 = -24/8

n = -3

User Asri Badlah
by
5.6k points
6 votes

Answer:

-3 = n

Explanation:

11(n − 1) + 35 = 3n

Distribute

11n -11 +35 = 3n

Combine like terms

11n +24 = 3n

Subtract 11n from each side

11n -11n +24 = 3n -11

24 = -8n

Divide by -8

24/-8 = -8n/-8

-3 = n

User ZiggyTheHamster
by
5.7k points